The impact of pH on cytotoxic effects of three root canal irrigants - Mohammad Ali Saghiri; Abbas Delvarani; Payman Mehrvarzfar; Mohsen Nikoo; Mehrdad Lotfi; Kasra Karamifar; Kamal Asgar; Sahar Dadvand (Saudi Dental Journal)
Aim: Cytotoxicity of root canal irrigants is important due to their close contact with host tissues. This study was to assess the possible impact of pH on cytotoxic effects of MTAD, 17% EDTA, and 2.6% NaOCl on the human gingival fibroblasts using MTT assay. Materials and methods: Human gingival fibroblasts were exposed to the irrigants and their viability was assessed after 1, 6, and 12 h. The pH of the medium was measured in each interval. Light absorption values were measured for each culture medium using Elisa Reader device. Results: NaOCl had significantly less cytotoxicity than EDTA and MTAD. Also irrigants cytotoxicity decreased in 12, 1, and 6 h, respectively. Conclusion: It seems that variation of the pH resulted in variation in the cytotoxicity of solutions; i.e., it follows the pattern of the pH variation. Keywords: Cytotoxicity, Ethylene diaminetetra acetic acid, MTAD, pH, Sodium hypochlorite